Evaluation of shrinkage-induced stress in a runway repaired using compliant polymer concrete. (15th December 2016) - Jung, Kyung-Chae; Chang, Seung-Hwan
Abstract: The aim of this study is to investigate shrinkage-induced stresses in a part of a runway pavement repaired using compliant polymer concrete. For this purpose, material properties of partially cured polymer concrete at different degrees of cure during the cure process were estimated and used in the stress analysis. To measure the degree of cure and shrinkage strain in the repaired part, a monitoring system comprising dielectrometry and fiber Bragg grating (FBG) optic sensors was installed in an airport (Gimpo airport, Korea). The shrinkage strain values measured at the various degrees of cure of the polymer concrete were used in finite element analysis to estimate shrinkage-induced stresses. To improve accuracy of stress analysis, property change of the polymer concrete during the curing process were also considered. It was concluded that property variations during the curing process should be considered for estimating material failure because the cure shrinkage of the repair material induces tensile stress following the critical loading pattern of concretes.